2017
DOI: 10.1039/c6nr09021d
|View full text |Cite
|
Sign up to set email alerts
|

Band-edge oscillator strength of colloidal CdSe/CdS dot-in-rods: comparison of absorption and time-resolved fluorescence spectroscopy

Abstract: We studied the oscillator strength f of the band gap transition in heteronanocrystals (hNCs) with a spherical CdSe core embedded in an elongated CdS shell. A comparison with f of core-only CdSe NCs confirmed a reduction of the electron-hole overlap in hNCs with a band gap larger than 2.05 eV or smaller than 1.98 eV. However, the decrease in f is limited to about 50% when compared to CdSe NCs, suggesting that residual confinement still localizes the electron near the core. We correlated f with the radiative lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…spectroscopy) measurements (See supplementary materials for more details) [53][54][55] . The absorption cross section of non-fused dimers (green Fig.…”
Section: Please Cite This Article As Doi:101063/15128086mentioning
confidence: 99%
See 1 more Smart Citation
“…spectroscopy) measurements (See supplementary materials for more details) [53][54][55] . The absorption cross section of non-fused dimers (green Fig.…”
Section: Please Cite This Article As Doi:101063/15128086mentioning
confidence: 99%
“…However, the online version of record will be different from this version once it has been copyedited and typeset. PLEASE CITE THIS ARTICLE AS DOI:10.1063/1.5128086 spectroscopy) measurements (See supplementary materials for more details) [53][54][55] . The absorption cross section of non-fused dimers (green Fig.…”
Section: Please Cite This Article As Doi:101063/15128086mentioning
confidence: 99%
“…The transition from delocalised (quasi type-II regime) to localised electrons (type-I regime) occurs between CdSe seed sizes of 3 to 4 nm. 6,9,10 A similar system in which electrons and holes separate spatially at a heterointerface with staggered band alignment (type-II structure) has been fabricated using ZnSe nanocrystals as seeds in ZnSe/CdS nanorods. 5,11,12 Different interpretations exist in the literature concerning the delocalisation and spatial separation of electrons and holes in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, all reported lifetimes for CdSe/CdS support coulomb-bound excitons and holes localised in the potential well of the seed particles. 10 Charge carrier dynamics are further complicated by surface states. It was shown that in pure CdS nanorods over 99% of the photoexcited holes get trapped in surface states within the first picoseconds after excitation, which is observed using TA spectroscopy as a weak, broad photoinduced absorption below the band gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation